La création du CAPES de langues kanak et les problématiques qu’elle pose sur la gestion des langues dites régionales - Yann Bévant (Lengas)
Since the 1988 Matignon-Oudinot Accords and the 1998 Noumea Agreement, New Caledonia –also called Kanaky by pro-independence people-, has enjoyed a very specific status within the constitutional framework of the French Republic. These Accords led to a period of appeasement and to autonomous consociational politics, which put an end to a situation nearing civil war at the beginning of the 1980s. They acknowledged the legitimacy of a decolonisation process and of a territorial right to self-determination. This process has recently culminated in three referenda, which have in fact failed to clear the path for the future of the archipelago, in spite of the French government’s claims.Implements were created in order to acknowledge the specific identity of the territory. The teaching certificate in Kanak languages is one of these tools this paper seeks to explore, as it epitomizes existing contradictions in the process of decolonisation. The latter, though it is supposed to give back their place to key local actors and aspects of Kanak culture, remains informed by an utterly centralised organisational pattern.